2020
DOI: 10.1021/acs.inorgchem.9b03747
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation by H5[PV2Mo10O40] in a Highly Acidic Medium

Abstract: Dissolution of the polyoxometalate (POM) cluster anion H 5 [PV 2 Mo 10 O 40 ] ( 1 ; a mixture of positional isomers) in 50% aq H 2 SO 4 dramatically enhances its ability to oxidize methylarenes, while fully retaining the high selectivities typical of this versatile oxidant. To better understand this impressive reactivity, we now provide new information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…32 Interestingly, work by Tiwari et al on polyoxometalate structures, specifically H 5 ijPV 2 Mo 10 O 40 ], have shown that the dissolution of two reactive pervanadyl ions by H 2 SO 4 is a reversible process, which can be controlled by the pH. 33 Vanadium bronzes, which when combined with other metals such as sodium, copper or silver, can show stability in aqueous media and have various applications in areas such as, photocatalysts and in electrochemical energy storage, however elemental analysis of aqueous media is not always reported. 34,35 In this report we show the synthesis of several vanadium bronzes with the aim of achieving stabilisation in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…32 Interestingly, work by Tiwari et al on polyoxometalate structures, specifically H 5 ijPV 2 Mo 10 O 40 ], have shown that the dissolution of two reactive pervanadyl ions by H 2 SO 4 is a reversible process, which can be controlled by the pH. 33 Vanadium bronzes, which when combined with other metals such as sodium, copper or silver, can show stability in aqueous media and have various applications in areas such as, photocatalysts and in electrochemical energy storage, however elemental analysis of aqueous media is not always reported. 34,35 In this report we show the synthesis of several vanadium bronzes with the aim of achieving stabilisation in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…The changes of conductivity on the pPy film coated on the nitrocellulose membrane were first quantified by four-point probe method. It was determined that the intrinsic reactivity of H 2 O 2 with pPy was too slow, and hence we added phosphovanado­molybdate (H 5 [PV 2 Mo 10 O 40 ]) as a water-soluble oxidation (redox) catalyst that has been shown to be compatible with oxidases. , The phosphovanado­molybdate solution was premixed with glucose solutions before being applied to the test strips. Table and Table S2 detail the conductivity changes observed with different concentrations of glucose or sodium pyruvate.…”
Section: Resultsmentioning
confidence: 99%
“…This work highlights how POM-SACs or POM-SSCs could be utilized for dynamic coordination chemistry and on-demand delivery of reactive molecular species. [97] [93] b) Five structural isomers of the oxidation catalyst H 5 [V 2 PMo 10 O 40 ]. [78]…”
Section: From Pom-single Atom Catalysts To Pom-single-site Catalystsmentioning
confidence: 99%